PEREMPUAN DAN KEKERASAN DALAM RUMAH TANGGA - Ana Rochayati Nur Faisyah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2022)
The issue of the importance of addressing domestic violence (KDRT) in modern society is a form of liberation for women. Modern society is introduced to various perspectives and various interpretations of things that can help women to dare to come out of their domestic space. Women as victims of domestic violence cases are the result of various aspects in different dimensions. Starting from the negative stigma against the existence of women, the scope of which revolves around the domestic area to how religious texts are understood and the patriarchal culture that develops in the public sphere. This article aims to analyze how these things can trigger domestic violence experienced by women as victims. This article uses a feminist discourse analysis approach with qualitative research as a form of elaboration of religious literature. This study discusses three main problems. First, domestic violence against women as the result of patriarchal cultural discourse. Second, domestic violence in Islamic discourse. Third, the impact of domestic violence on women. This study seeks to emphasize that violence in any form in general, and domestic violence in particular, from an Islamic perspective cannot be justified